Clinical Rehabilitation Nursing of Patients with Chronic Obstructive Pulmonary Disease Based on Intelligent Medicine - Lingyan Zhao; Liyan Chu (Applied Bionics and Biomechanics)
Chronic obstructive pulmonary disease (COPD) is a respiratory disease that can be treated and prevented. The purpose of this paper is to conduct a meta-analysis of clinical rehabilitation nursing of COPD patients based on intelligent medical care by constructing a suitable model so as to make the research on clinical nursing of COPD patients more effective. This paper first introduced the intelligent medical system, analyzed the clinical rehabilitation nursing of COPD patients, established the SCNet model suitable for this paper, and then used statistical algorithms to carry out the meta dynamic analysis of the clinical rehabilitation nursing for COPD patients. Through the analysis of the current situation of medical equipment and the comparison of models and statistical analysis, the experimental results showed that the pulmonary function indexes of the pulmonary rehabilitation treatment group and the conventional treatment group were improved after treatment compared with before treatment. Although on specificity metrics SCNet did not perform the best, it was about 1% lower than the best baseline model. However, the comprehensive performance of the SCNet model on Acc, Sen, F1-Score, and AP indicators showed that the model SCNet proposed in this paper had certain advantages, which was helpful for the clinical rehabilitation care of patients with COPD and could better assist doctors in treatment.